Ice Core Records of West Greenland Melt and Climate Forcing. Issue 7 (6th April 2018) - Graeter, K. A.; Osterberg, E. C.; Ferris, D. G.; Hawley, R. L.; Marshall, H. P.; Lewis, G.; Meehan, T.; McCarthy, F.; Overly, T.; Birkel, S. D.
Abstract: Remote sensing observations and climate models indicate that the Greenland Ice Sheet (GrIS) has been losing mass since the late 1990s, mostly due to enhanced surface melting from rising summer temperatures. However, in situ observational records of GrIS melt rates over recent decades are rare. Here we develop a record of frozen meltwater in the west GrIS percolation zone preserved in seven firn cores. Quantifying ice layer distribution as a melt feature percentage (MFP), we find significant increases in MFP in the southernmost five cores over the past 50 years to unprecedented modern levels (since 1550 CE). Annual to decadal changes in summer temperatures and MFP are closely tied to changes in Greenland summer blocking activity and North Atlantic sea surface temperatures since 1870. However, summer warming of 1.2°C since 1870–1900, in addition to warming attributable to recent sea surface temperature and blocking variability, is a critical driver of high modern MFP levels. Plain Language Summary: Computer models and satellites show that the amount of snow melting each summer on Greenland has increased since the 1990s, but it is difficult to confirm this directly on the ice sheet. When surface snow melts, the water spreads into deeper layers of snow and refreezes as an ice layer. As fresh snow buries each summer's ice layers, the history of snowmelt is preserved in the ice sheet. We describe seven ice cores collected from western Greenland that contain the history of ice layers back to 1966. We find more ice layers, caused by more summer melting, since the 1990s. By comparing our ice cores to a longer ice core from the same area, we show that today's melt rates are the highest in this region since at least 1550 CE. Year‐to‐year changes in the amount of melting are mostly caused by changes in the number of summer high‐pressure systems and fluctuating ocean temperatures near Greenland. Although both of these processes have contributed to recent high melt rates, Greenland is 1.2°C warmer today than during similar conditions in the 1890s. This "extra" warming is most likely caused by human greenhouse gas emissions, leading to the unusual melt rates of recent years. Key Points: Ice cores from the West Greenland percolation zone confirm a significant increase in surface melt rates since the early 1990s Modern melt rates in West Greenland are unmatched in a composite ice core melt record back to 1550 CE Greenland blocking, regional sea surface temperatures, and a long‐term summer warming trend are required to explain modern melt rates